A comparative study on patient safety culture among high-risk hospital staff in the context of the COVID-19 and non-COVID-19 pandemic: a cross-sectional study in Taiwan - Huang, Chih-Hsuan; Wu, Hsin-Hung; Lee, Yii-Ching (Frontiers in Public Health, 2023)
The study aimed to compare the evolution of patient safety culture perceived by high-risk hospital staff in the context of the COVID-19 pandemic and non-COVID-19 pandemic and to examine the variations in patient safety culture across demographic variables. The study found that the COVID-19 pandemic has significantly impacted patient safety culture in healthcare settings, with an increased focus on safety climate, job satisfaction, teamwork climate, stress recognition, and emotional exhaustion. Safety culture and work stress vary among medical professionals of different age groups. To reduce stress, workload should be minimized, work efficiency improved, and physical and mental health promoted. Strengthening safety culture can reduce work-related stress, improve job satisfaction, and increase dedication towards work. The study recommends interventions such as psychological and social support, along with emotional management training, to reduce emotional exhaustion. Healthcare institutions can set up psychological counseling hotlines or support groups to help medical professionals reduce stress and emotional burden.